Immunophenotypic, immunocytochemistry, ultrastructural, and cytogenetic characterization of mesenchymal stem cells from equine bone marrow - Maia, Leandro [UNESP]; Landim-Alvarenga, Fernanda C. [UNESP]; Mota, Ligia S. L. Silveira da [UNESP]; Golim, Marjorie de Assis [UNESP]; Laufer-Amorim, Reneé [UNESP]; Vita, Bruna de [UNESP]; Barberini, Danielle Jaqueta [UNESP]; Listoni, Amanda Jeronimo [UNESP]; Moraes, Carolina Nogueira de [UNESP]; Heckler, Marta Cristina Thomas [UNESP]; Amorim, Rogerio Martins [UNESP] (Wiley, 2013)
The aim of this study was to isolate, culture, and characterize mesenchymal stem cells (MSCs) from horse bone marrow (BM) using the techniques of flow cytometry, immunocytochemistry, cytogenetics, and electron microscopy. Immunophenotypic analysis revealed the presence of MSCs with high expression of the CD90 marker, lower expression of the CD44 marker, and absent expression of the CD34 marker. In assays of differentiation, the positive response to osteogenic (OST), chondrogenic (CDG), and adipogenic (ADP) differentiation signals was observed and characterized by deposition of calcium-rich extracellular matrix (OST), proteoglycans and collagen II (CDG) and intracellular deposition of fat drops (ADP). In immunocytochemical characterization, MSCs were immunopositive for CD44, vimentin, and PCNA, and they were negative for CD13. In the ultrastructural analysis of MSCs, the most outstanding characteristic was the presence of rough endoplasmic reticulum with very dilated cisterns filled with a low electrodensity material. Additionally, MSCs had normal karyotypes (2n=64) as evidenced by cytogenetic analysis, and aneuploidy in metaphase was not observed. The protocols for isolating, culturing, and characterizing equine MSCs used in this study were shown to be appropriate for the production of a cell population with a good potential for differentiation and without aneuploidy that can be used to study future cellular therapies. © 2013 Wiley Periodicals, Inc.
Keywords: Differentiation; Horse; Isolation; Mesenchymal stem cells; Surface marker; Equidae